Fog‐enabled vehicular networks: A new challenge for mobility management. Issue 6 (17th January 2020) - Aljeri, Noura; Boukerche, Azzedine
Abstract : With the increasing presence of latency‐critical applications and services along with the high demand for ubiquitous connectivity, a new challenge arise in the design of the next generation of vehicular networks. The requirements of low latency services and powerful computational functionalities have decreased the performance of cloud centers, being unable to satisfy the fast growing number of vehicles on roads and road assistance based applications. Vehicular Fog Networks is an emerging network architecture that elevates the burden on the cloud and shifts Cloud services to the edge of the network. However, the integration of fog‐computing and vehicular networks raises several issues and challenges, including mobility management. In this paper, we provide insights into the latest solutions for mobility management protocols in fog‐enabled vehicular networks. Then, we explore related open issues and point out future research directions.